Impact of axillary node-positivity and surgical resection margins on survival of women treated for breast cancer in Ibadan, Nigeria (2020)
Introduction: Oncologic surgical extirpation, the mainstay of loco-regional disease control in breast cancer, is aimed at achieving negative margins and lymph node clearance. Even though axillary lymph nodal metastasis is a critical index of prognostication, establishing the impact of lymph node ratio (LNR) and adequate surgical margins on disease specific survivorship would be key to achieving longer survival. This study examines the prognostic role of pN (lymph nodes positive for malignancy), LNR and resection margin on breast cancer survival in a tertiary hospital in Ibadan, Nigeria. Methods: We conducted a longitudinal cohort study of 225 patients with breast carcinoma, documented clinico-pathologic parameters and 5-year follow up outcomes – distant metastasis and survival. Chi-square test and logistic regression analysis were used to evaluate the interaction of resection margin and proportion of metastatic lymph nodes with patients’ survival. The receiver operating characteristic curve was plotted to deter mine the proportion of metastatic lymph nodes which predicted survival. The survival analysis was done using Kaplan–Meier method. Results: Sixty (26.7%) patients of the patients had positive resection margins, with the most common immuno-histochemical type being Lumina A. 110 (49%) patients had more than 10 axillary lymph nodes harvested. The mean age was 48.6 + 11.8 years. Tumour size (p = 0.018), histological type (p = 0.015), grade (p = 0.006), resection margin (p = 0.023), number of harvested nodes (p < 0.01), number of metastatic nodes (p < 0.001) and loco-regional recurrence (p < 0.01) are associated with survival. The overall 5-year survival was 65.3%. Conclusion: Unfavourable survival outcomes following breast cancer treatment is multifactorial, including the challenges faced in the multimodal treatment protocol received by our patients.